Pratique de l'amour: le plaisir et l'inquiétude - Bozon, Michel (Payot, 2016)
"Le coup de foudre, seule une petite minorité des couples disent l'avoir éprouvé. Comment l'immense majorité des autres font-ils donc pour devenir amoureux? Pour Michel Bozon, l'amour est une pratique et une histoire : pas seulement une émotion ou un sentiment, mais aussi, et surtout, une affaire permanente d'interprétation et d'échanges - d'informations personnelles, de cadeaux, de sexe -, qui évoluent dans la durée ; dès les débuts amoureux, l'abandon de soi est intimement lié à l'emprise sur l'autre. S'appuyant sur la littérature, le cinéma, les témoignages et les résultats des enquêtes sociologiques, 'Pratique de l'amour' éclaire aussi la vie amoureuse dans les relations et les couples stables, faite d'intermittences, d'engagements et de désengagements successifs. Le plaisir amoureux n'est jamais exempt d'inquiétude. Au final, Michel Bozon montre que l'amour est progressif, il s'apprend, il se construit, mais il peut aussi se défaire ..."
Keywords: 2000 à aujourd'hui; 2000-2009; 2010-2019; approches et analyses; cours; discipline; europe; france; hétérosexualité; premier cycle; privilèges; périodes historiques; relations amoureuses; régions géographiques; sciences humaines; sexualité; soc2262; sociologie; systèmes d'oppressions; thématiques

« Gender Equality and Economic Inequality: Impact on Marriage » dans Gender and couple relationships - Coontz, Stephanie (Gender and couple relationships, 2016)
Changes in aggregate marriage rates and in the internal dynamics of individual marriages should be understood as the outcome of two powerful but very different trends in gender and class relations. One trend is the uneven but undeniably dramatic progress toward equality in personal life and cultural values, which has led to widespread repudiation of centuries-old gender hierarchies. The other trend is an equally powerful movement toward growing inequality, insecurity, and unpredictability in economic life, which has resulted in substantial losses for the most historically vulnerable and least-educated sections of the workforce. The ongoing gender revolution interacts with widening economic inequality in complex ways, increasing the benefits of marriage for individuals with higher earning power while increasing the risks of marriage for low-income individuals, especially women.
Keywords: 1900-1999; 1980-1989; 1990-1999; 2000 à aujourd'hui; 2000-2009; amérique du nord; amériques; approches et analyses; care; cours; discipline; discours dominant; droits des femmes*; famille; inégalités; mariage; premier cycle; privilèges; périodes historiques; rapports sociaux de sexe; régions géographiques; sciences humaines; sexualité; soc2262; sociologie; systèmes d'oppressions; thématiques; états-unis

Navigating gender and sexuality in the classroom: Narrative insights from students and educators - McEntarfer, Heather Killelea (Routledge, 2016)
Gender identity and sexuality play crucial roles in the educational experiences of students, parents, and teachers. Teacher education must more directly address the ways that schools reflect and reproduce oppressive gender norms, working to combat homophobia, transphobia, heteronormativity, and gendered expectations in schools. This volume examines teacher candidates’ experiences with gender and sexuality in the classroom, offering insight and strategies to better prepare teachers and teacher educators to support LGBTQ youth and families. This volume addresses the need for broader, more in-depth qualitative data describing teacher candidates’ responses to diversity in the classroom (including gender, sexuality, race, class and religion). By using pedagogical tools such as narrative writing and positioning theory, teacher candidates explore these issues to better understand their own students’ narratives in deeply embodied ways. This book calls for schools to be places where oppression, in all its complexity, is explored and challenged rather than replicated.
Keywords: LGBTQIA2+; approches et analyses; discipline; formations; hétérosexisme; identités LGBTQIA2+; intersectionnalité; outils; outils didactiques; privilèges; pédagogie; religion; sciences de l'éducation; sexualité; systèmes d'oppressions; thématiques